Financial efficiency of Polish enterprises operating in the transport and warehouse sector in the conditions of the Russian-Ukraine war - Adam Zając; Marta Idasz-Balina; Rafał Balina; Adrian Sadłowski (Journal of Business Economics and Management, 2025)
The study aimed to identify the dependence of the financial results of Poland’s transport and warehousing sector on the current macroeconomic situation and security conditions related to the war in Ukraine. The econometric method was used – a dynamic panel model. Data from January 1, 2007, to June 30, 2023, from the Central Statistical Office and the National Bank of Poland were used. It was found that the impact of macroeconomic factors on the financial efficiency of individual industries in Poland’s warehouse and transport sector varies in terms of direction and strength of effects. Key factors were identified as macroeconomic determinants of the financial condition of this sector and industries (subsectors) sensitive to hostilities in Ukraine were indicated. The implications of the findings for decision-makers, investors, businesses and researchers are outlined.